2017
DOI: 10.1002/ghg.1749
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on hybrid MS‐CA system for post‐combustion CO2 capture

Abstract: A lab‐scale hybrid membrane separation‐chemical absorption (MS‐CA) system for a post‐combustion process was implemented by combining a hollow‐fibre membrane module and a packed column in series. A solution‐diffusion model and double‐film theory were adopted to investigate the mass‐transfer performance of membrane separation and the chemical absorption process. To determine optimal operational conditions, experiments were conducted to investigate the mass transfer characteristics and CO2 removal of both mono‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Recently, Jiang et al . 2018 experimentally investigated a lab‐scale membrane‐chemical absorption hybrid system using a hollow fiber membrane in series with the packed column to measure mass transfer characteristics and optimal operating conditions of the hybrid system. Their results indicated that a CO 2 removal efficiency of 99.49% can be achieved at optimal operating temperature of 40°C, MEA concentration of 10 wt%, and feed gas pressure of 1 MPa.…”
Section: Hybrid Techniques For Co2 Capturementioning
confidence: 99%
“…Recently, Jiang et al . 2018 experimentally investigated a lab‐scale membrane‐chemical absorption hybrid system using a hollow fiber membrane in series with the packed column to measure mass transfer characteristics and optimal operating conditions of the hybrid system. Their results indicated that a CO 2 removal efficiency of 99.49% can be achieved at optimal operating temperature of 40°C, MEA concentration of 10 wt%, and feed gas pressure of 1 MPa.…”
Section: Hybrid Techniques For Co2 Capturementioning
confidence: 99%